2017 Opto-Electronics and Communications Conference (OECC) and Photonics Global Conference (PGC) 2017
DOI: 10.1109/oecc.2017.8115015
|View full text |Cite
|
Sign up to set email alerts
|

RZ-DPSK optical modulation for free space optical communication by satellites

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Similarly, it may also be noticed from Figure 5(b), (c) that for both higher values of the turbulence, downlink channels that are DPSK modulated perform better than the uplink channels that are OOK modulated. This trend has also been observed in other studies especially under strong turbulence conditions [25,26]. To further elaborate the effect of FSO impairments on the received signals, Figure 6 presents the eye-diagrams of the downlink and uplink channels at different values of turbulence.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly, it may also be noticed from Figure 5(b), (c) that for both higher values of the turbulence, downlink channels that are DPSK modulated perform better than the uplink channels that are OOK modulated. This trend has also been observed in other studies especially under strong turbulence conditions [25,26]. To further elaborate the effect of FSO impairments on the received signals, Figure 6 presents the eye-diagrams of the downlink and uplink channels at different values of turbulence.…”
Section: Resultssupporting
confidence: 79%
“…It has been observed that the downlink channels require very low receiver sensitivities while the uplink channels require high values of receiver sensitivities at high turbulence since they propagate twice the FSO distance compared to the downlink channels. Furthermore, DPSK modulation performs better than the OOK modulation under strong turbulence conditions as demonstrated in previous studies as well [25,26]. Gamma-Gamma channel is used to model the turbulence of the FSO links.…”
Section: Discussionmentioning
confidence: 62%
“…Optical link models have been used to predict the communication performance 7 . The OOK transmitter was made up of a CW DFB laser and a Mach-Zehnder intensity modulator, and the receiver included a pre-amplification stage based on a low-noise Erbium Doped Fiber Amplifier (EDFA).…”
Section: Ook/dpsk Optical Communication Link Simulationsmentioning
confidence: 99%
“…In addition, two different duty cycles can be considered for this transmitter: Non-Return-to-Zero (NRZ) and 50% RZ OOK thanks to two Mach Zehnder Modulator (MZM). More information about this communication transmitter can be found in [15]. The propagation emulator channel is modeled by two different variable optical attenuators (VOA): the first is used to introduce the atmospheric attenuation and all static mitigation, the second one is to emulate the random mitigation due to phase screen deformation (Tip/Tilt) and its correction with adaptive optics system.…”
Section: Optical Link Simulationmentioning
confidence: 99%